A real-world examination of progressive imagery delivery in competitive basketball - Fazel, F.; Morris, T.; Watt, A. P.; Maher, R. (Asian Journal of Sport and Exercise Psychology, 2022)
Effective delivery of imagery training has been studied for some time. Recently, researchers have determined that, in some contexts, Progressive Imagery (PI), in which content is added to the imagery script in phases, can be more effective than Routine Imagery (RI), in which all the imagery content is presented in every session of an imagery program. However, most research to date consists of field studies, lacking ecological validity. We examined the efficacy of a PI program presented to highly-skilled basketball players in league competition across a whole season, using a Single-Case Design (SCD). Participants were five male players from Division 1 of the State Basketball League, who were pre-tested on the Sport Imagery Ability Measure (SIAM) to ensure they had at least moderate imagery ability. We monitored their Free-Throw Shooting (FTS) percentage in every league match of the whole season. The first 4 to 6 matches (Phase A) gave a stable baseline. Phase B, again lasting 4 to 6 matches, involved imagery that focused on static aspects of FTS movements. In Phase C (4 to 6 matches), more complex elements of FTS were added to imagery, including teammates and opponents on court. Phase D, lasting at least 4 matches, introduced imagery of a high-pressure context in which the FTS shot would decide the match. At the end of the season, each participant was interviewed about his experiences with imagery. We employed visual analysis and the split-middle technique to measure performance and self-efficacy. On these measures, all participants improved their FTS from baseline to Phase D, although two performed best in Phase C. Participants reported feeling comfortable with the changing phases, although one commented that he would have preferred the high-pressure imagery earlier, before he faced real high-pressure finals. We concluded that PI was an effective intervention among highly-skilled participants over a full competition season, while timing of high-pressure imagery should be tested prior to crucial season-ending matches.